Design and analysis of an arduino-based low-cost true random number generator - Kaner, Seyfullah; Garıpcan, Ali Murat; Erdem, Ebubekir (Munzur Üniversitesi, 2026)
[Abstract Not Available]
Keywords: Güvenilir Sistemler